Женщины Лазаря: роман / Мария Степнова - Степнова Марина Львовна (Проза Марины Степновой, 2015)
Экземпляры: аб. (20151022) / Инвентарный номер: 56720 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: С 79 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44